Human pegivirus-1 (HPgV-1, GBV-C) RNA prevalence and genotype diversity among volunteer blood donors from an intra-hospital hemotherapy service in Southern Brazil. (April 2019) - Slavov, Svetoslav Nanev; Silveira, Roberta Maraninchi; Rodrigues, Evandra Strazza; Diefenbach, Cristiane Fração; Zimmermann, Ana Maria; Covas, Dimas Tadeu; Kashima, Simone
Abstract: Objective: Human pegivirus (HPgV-1, GBV-C) is classified within the Pegivirus genus of the Flaviviriade family. The natural history of HPgV-1 infection is still unclear, however, the main route of viral transmission seems to be the parenteral one. The detection of HPgV-1 viremia in blood donors without parenteral exposure demonstrates that other routes of HPgV-1 transmission might also exist. The objective of the present study was to evaluate the prevalence of HPgV-1 RNA and circulating genotypes among blood donors from a intra-hospital Hemotherapy Service localized in the Santa Maria city, central part of the Rio Grande do Sul State in the extreme South of Brazil. Methods: Blood samples were obtained from 373 volunteer blood donors and tested for the presence of HPgV-1 RNA. All positive for RNA samples were submitted to sequencing and phylogenetic analysis. Results: The prevalence of the HPgV-1 RNA was 5.9% (22/373). The performed phylogenetic analysis demonstrated a predominant detection of genotype 2 with its both subgenotype forms (95.5% of all isolates i.e 54.5% belonging to subgenotype 2 A and 40.9% belonging to subgenotype 2B). Only one sequence was classified as genotype 3 (1/22, 4.5%). Conclusions: Our study demonstrates the circulation pattern and genotypes of HPgV-1 among volunteer blood donors of South Brazil, and adds to the global knowledge of the natural history and possible transmission routes of this viral agent with putative impact on the area of hemotherapy.